2020
DOI: 10.1007/s11102-020-01044-0
|View full text |Cite|
|
Sign up to set email alerts
|

Quality of care evaluation in non-functioning pituitary adenoma with chiasm compression: visual outcomes and timing of intervention clinical recommendations based on a systematic literature review and cohort study

Abstract: Purpose Surgery in patients with non-functioning pituitary macroadenomas (NFMA) is effective in ameliorating visual function. The urgency for decompression, and preferred timing of surgery related to the preoperative severity of dysfunction is unknown. Methods Systematic review for evidence to provide clinical guidance for timing of surgical decompression of the optic chiasm, and a cohort study of 30 NFMA patients, in whom mean devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…8 Cranio-caudal dimension of the NPFA, which determines the degree of compromise of the visual apparatus, clearly correlated with visual field defects in our series as also shown in a recent systematic review which examined 44 studies with a total of 4789 patients. 29 Neither age nor tumour volume had any correlation with endocrine dysfunction (such as hypogonadism, hypothyroidism or adrenal insufficiency) or headaches as shown by previous studies. 13,30 Functional recovery in at least one of the endocrine deficits after transsphenoidal surgery in 24% of patients in our cohort is comparable with the studies by Little et al 11 and Najmaldin et al 13 However, other authors reported higher rates of hormonal recovery, 12,31,32 probably because of the tumour characteristics in the individual cases these series.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…8 Cranio-caudal dimension of the NPFA, which determines the degree of compromise of the visual apparatus, clearly correlated with visual field defects in our series as also shown in a recent systematic review which examined 44 studies with a total of 4789 patients. 29 Neither age nor tumour volume had any correlation with endocrine dysfunction (such as hypogonadism, hypothyroidism or adrenal insufficiency) or headaches as shown by previous studies. 13,30 Functional recovery in at least one of the endocrine deficits after transsphenoidal surgery in 24% of patients in our cohort is comparable with the studies by Little et al 11 and Najmaldin et al 13 However, other authors reported higher rates of hormonal recovery, 12,31,32 probably because of the tumour characteristics in the individual cases these series.…”
Section: Discussionmentioning
confidence: 59%
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27] Tumour size was also found to influence postoperative visual recovery in previous studies. 28,29 However, there is discrepancy in the reported effects of age and tumour volume on preoperative headache, endocrine symptoms, and the recovery/ improvement of these postoperatively. 11,13,[30][31][32] Therefore, we share the experience in managing NFPAs in our regional referral centre in the United Kingdom (UK) outlining the pre-and postsurgical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The HFA perimetry, initially developed for glaucoma patients, allows a more exact outcome and comparison [40,41]. Recent studies show that this scale can also be used to investigate VFs in patients with pituitary adenomas [33]. Reason to use the MD instead of the VFI was because MD scores have been measured during the whole follow-up period of the patients in this study, where the VFI has been introduced in 2011.…”
Section: Discussionmentioning
confidence: 99%
“…The MD score depicts the VFs compared to a healthy control group. A recent literature study showed that this score can be used to assess the VF for patients with pituitary adenomas [33]. Unreliable measurements, based on loss of fixation, falls positive and falls negative measurements, were excluded, as reviewed by two independent observers (M.T., I.C.N).…”
Section: Visual Function Assessmentsmentioning
confidence: 99%
“…Non-secreting tumors usually do not present until they are sufficiently large enough to cause neurological deficits by mass effect. They also can be classified according to size for microadenoma less than one centimeter, macroadenoma more than 1cm and giant adenoma more than 4cm [4][5] . Giant pituitary adenomas are defined as tumors larger than 4 cm that usually extend within 6 mm of the foramen of Monro.…”
Section: Introductionmentioning
confidence: 99%